Isolation, Identification, Anti-Inflammatory, and In Silico Analysis of New Lignans from the Resin of Ferula sinkiangensis - Junchi Wang; Qi Zheng; Minghui Shi; Huaxiang Wang; Congzhao Fan; Guoping Wang; Yaqin Zhao; Jianyong Si (MDPI AG, 2023)
Ferula sinkiangensis K. M. Shen (Apiaceae) is distributed in arid desert areas of Xinjiang, and its resin is a traditional Chinese medicine to treat gastrointestinal digestive diseases. To explore bioactive components from F. sinkiangensis, three new lignans and thirteen known components were isolated. The structural elucidation of the components was established utilizing spectroscopic analyses together with ECD calculations. Griess reaction results indicated new compounds 1 and 2 significantly decreased NO production in LPS-stimulated RAW 264.7 macrophages, and ELISA results indicated that they effectively attenuated LPS-induced inflammation by inhibiting TNF-α, IL-1β, and IL-6 expressions. The in silico approach confirmed that compound 1 docked into the receptors with strong binding energies of −5.84~−10.79 kcal/mol. In addition, compound 6 inhibited the proliferation of AGS gastric cancer cells with IC50 values of 15.2 μM by suppressing the cell migration and invasion. This study disclosed that F. sinkiangensis might be a promising potential resource for bioactive components.